Anthrenus museorum - Majka, Christopher G. (Zenodo, 2007)
Anthrenus museorum (Linnaeus, 1761) NOVA SCOTIA: Colchester Co.: Debert, 13.v.1996, J. Ogden, JOC. PRINCE EDWARD ISLAND: Queens Co.: Brackley, 9.vii.1983, M.E.M. Smith, ACPE; Charlottetown, 16.ii.1996 and 11.iv.1997, M.E.M. Smith, (2), ACPE; Cornwall, summer 1998, M.E.M. Smith, (3), ACPE. An introduced Palearctic species, newly recorded in Nova Scotia, Prince Edward Island, and the Maritime Provinces as a whole (Fig. 4). In the USA recorded from Connecticut, Massachusetts, and Wisconsin (Beal 2003); in Canada known from Ontario, Québec, and Newfoundland (Bousquet 1991). A household pest; larvae are found on wool, fur, skins, and other animal products; also on museum specimens and insect collections. Like other species in the genus, adults feed on nectar and pollen, mate in the field, and fly indoors to oviposit (Bousquet 1990). : Published as part of Majka, Christopher G., 2007, The Derodontidae, Dermestidae, Bostrichidae, and Anobiidae of the Maritime Provinces of Canada (Coleoptera: Bostrichiformia), pp. 1-38 in Zootaxa 1573 (1) on page 13, DOI: 10.11646/zootaxa.1573.1.1, http://zenodo.org/record/5096635 : {"references": ["Beal, R. S., Jr. (2003) Annotated checklist of Nearctic Dermestidae with revised key to the genera. The Coleopterists Bulletin, 57 (4), 391 - 404.", "Bousquet, Y. (1990) Beetles associated with stored products in Canada: an identification guide. Agriculture Canada Research Branch, Ottawa, Ontario. Publication 1837, 1 - 215."]}